2017
DOI: 10.1016/j.jaci.2016.07.025
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146a suppresses IL-17–mediated skin inflammation and is genetically associated with psoriasis

Abstract: Our results define a crucial role for miR-146a in modulating IL-17-driven inflammation in the skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
125
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(133 citation statements)
references
References 35 publications
5
125
1
2
Order By: Relevance
“…Upregulation of miR-203 in psoriatic plaques leads to downregulation of cytokine signaling 3 (SOCS-3), which is involved in inflammatory responses and keratinocyte functions (Sonkoly et al, 2007). Recently, Srivastava and colleagues (2016) unveiled the role of miR-146a in psoriasis patients and mouse model. They observed the genetic deletion of miR-146a leads to earlier onset and induced skin inflammation (Srivastava et al, 2016).…”
Section: Micrornas In Specific Tissues and Disease Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Upregulation of miR-203 in psoriatic plaques leads to downregulation of cytokine signaling 3 (SOCS-3), which is involved in inflammatory responses and keratinocyte functions (Sonkoly et al, 2007). Recently, Srivastava and colleagues (2016) unveiled the role of miR-146a in psoriasis patients and mouse model. They observed the genetic deletion of miR-146a leads to earlier onset and induced skin inflammation (Srivastava et al, 2016).…”
Section: Micrornas In Specific Tissues and Disease Processesmentioning
confidence: 99%
“…Recently, Srivastava and colleagues (2016) unveiled the role of miR-146a in psoriasis patients and mouse model. They observed the genetic deletion of miR-146a leads to earlier onset and induced skin inflammation (Srivastava et al, 2016). Further, miR-217 expression was found to be down-regulated in psoriasis keratinocytes of psoriatic patients (Zhu et al, 2016).…”
Section: Micrornas In Specific Tissues and Disease Processesmentioning
confidence: 99%
“…In human primary keratinocytes, miR-146a inhibits the expression of many pro-inflammatory factors, including CCL5 and IL-8 (Meisgen et al , 2014; Rebane et al , 2014). miR-146a has been shown to act as anti-inflammatory miRNA in mouse models of AD (Rebane et al , 2014), irritant contact dermatitis (Urgard et al , 2016) and psoriasis (Srivastava et al , 2016). The single nucleotide polymorphism (SNP) rs2910164 located in miR-146a precursor has been suggested to be associated with psoriasis in Han Chinese population (Zhang et al , 2014) and among Caucasians (Srivastava et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is known that activation of IL-17 signalling is central in the pathogenesis of psoriasis. A study using an imiquimodinduced mouse model of psoriasis showed that genetic deficiency in miR-146a could lead to an earlier onset and exacerbated skin lesions, with increased expression of IL-17-induced keratinocyte-derived inflammatory mediators [65,66]. In patients with RA, miR-146a has also been shown to be up-regulated in the IL-17-producing T cells [65,66].…”
Section: Aberrant Expression Of Mirnasmentioning
confidence: 99%
“…A study using an imiquimodinduced mouse model of psoriasis showed that genetic deficiency in miR-146a could lead to an earlier onset and exacerbated skin lesions, with increased expression of IL-17-induced keratinocyte-derived inflammatory mediators [65,66]. In patients with RA, miR-146a has also been shown to be up-regulated in the IL-17-producing T cells [65,66]. Therefore, miR-146a could play a negative ncRNAs in T cells of SLE and RA patients regulatory role in the inflammatory response by influencing the expression of IL-17 and TNF-a.…”
Section: Aberrant Expression Of Mirnasmentioning
confidence: 99%